Staphylococcus aureus and the Cutaneous Microbiota Biofilms in the Pathogenesis of Atopic Dermatitis - Di Domenico, Enea Gino (Microorganisms, 2019)
Biofilm is the dominant mode of growth of the skin microbiota, which promotes adhesion and persistence in the cutaneous microenvironment, thus contributing to the epidermal barrier function and local immune modulation. In turn, the local immune microenvironment plays a part in shaping the skin microbiota composition. Atopic dermatitis (AD) is an immune disorder characterized by a marked dysbiosis, with a sharp decline of microbial diversity. During AD flares biofilm-growing Staphylococcus aureus emerges as the major colonizer in the skin lesions, in strict association with disease severity. The chronic production of inflammatory cytokines in the skin of AD individuals concurs at supporting S. aureus biofilm overgrowth at the expense of other microbial commensals, subverting the composition of the healthy skin microbiome. The close relationship between the host and microbial biofilm resident in the skin has profound implications on human health, making skin microbiota an attractive target for the therapeutic management of different skin disorders.